KAJIAN KADAR AIR, WAKTU LARUT DAN RENDEMEN TEPUNG CANGKANG TELUR ITIK DENGAN METODE DAN WAKTU PEMASAKAN YANG BERBEDA - Nurmala, Nita; Santosa, R Singgih Sugeng; Setyaningrum, Agustinah (ANGON: Journal of Animal Science and Technology, 2021)
Background.This study aims to determine the interaction between cooking method and time, and the effect of cooking method and time on water content, dissolving time, and yield of duck eggshell flour. Materials and Methods. The materials used were 240g duck eggshells and aquadest. This study used an experimental method with a completely randomized design with a factorial pattern (2x4) consisting of 2 factors. Factor A=Cooking Method (M) with a factor level M1= Boiling Method and M2=Steaming Method, Factor B=Cooking Time (L) with a factor level L1=Cooking 0 minutes, L2=Cooking 10 minutes, L3=Cooking 20 minutes and L4=Cooking for 30 minutes, the treatment combination will be repeated 3 times. Data were analyzed using analysis of variance followed by further Orthogonal Polynomial and BNJ tests if they had a significant effect. Results. The results showed that the interaction between cooking method and time had a significant effect on water content, but had no significant effect on dissolving and yield time. The mean of research results for water content was 0.43%±0.25- 2.4%±0.66. The cooking method had a significant effect on dissolving time, but had no significant effect on water content and yield. The mean of research results for dissolving time was 8.81±0.38 seconds – 10.93±0.66 seconds. Cooking time had a significant effect on water content and yield, but had no significant effect on dissolving time. The average yield of the study was 97.53%±0.47-98.87%±0.06. Conclusion. The conclusion of this research is to produce good duck eggshell flour using the boiling method for 30 minutes, with the average result of water content of 1.03%±0.61, dissolving time of 7.75±1.67 seconds and yield of 98.2%±0.20.